The influence of model of eliciting activities on improving mathematical problem-solving ability - M. Taufik Qurohman; Prasetya Putra Nugraha; Syaefani Arif Romadhon; Ahmad Syahid Fathurrohman (International Journal of Trends in Mathematics Education Research, 2022)
The aims of this study is to improving problem-solving skills by combining the Model of Eliciting Activities (MEA) with Learning Model on the level of student independence. The technique used for sampling is cluster random sampling, namely by selecting two experimental classes and two control classes take one experimental class and one control class. Sample are students in grade 2A and 2B in Academic Year 2021/2022 with eigen-values material from Mechanical Engineering Study Program. In this study takes variables, namely problem-solving ability as a result with parameters i.e. with or without Model of Eliciting Activities (MEA). Data collection in unison with documentation, questionnaires, and test methods. And data processing using a two-way ANAVA 2 in unison with a 2x2 factorial design interaction as well as a determinant test using a benpheroni test. Based on the research, provide an understanding that students will gain learning in unison with the MEA get high problem-solving abilities than students Where students who get treatment with  learning is carried out conventionally, and students who have a high level of comfort have high problem-solving ability results abilities compared to  students who have a fairly low level of independence, so they have an influence on self-reliance and learning methods on students' problem solving Capabilities. Thus, students who have high comfort and get learning with the Eliciting Activities Model have a higher problem-solving ability compared to other types of learning interactions in this study.